Magnesium: a cation still forgotten in clinical practice! - Majda Bouhadjar; Rayan Mohamed Gheouali; Louiza Djerdjar (Journal de la Faculté de Médecine d'Oran)
Magnesium is among the trace elements that play a crucial role in the proper functioning of the body,it has long occupied a place of «forgotten cation» in medicine, in the absence of solid knowledge about its physiology and its potential therapeutic uses. In this article we report the results of recent data concerning its involvement in different biological functions.